Periodic Investigation of Properties of Oscillating Reactions: A 14-Membered Tetraazamacrocyclic Complex Catalyzed Zhabotinskii System - Hu, Gang; Qiang Xu, Zhi; Xie, Fu-Xing; Ni, She-Sheng; Zhang, Zu-De (Asian Journal of Chemistry, 2016)
The dependence of period of oscillation (T) on the initial concentrations of reactants for a Belousov-Zhabotinskii system is studied. This B-Z system is composed of sodium bromate, sulfuric acid, pyruvic acid and nickel(II) complex [NiL](ClO4)2, where L = 5,7,7,12,14,14-hexmethyl-1,4,8,11-tetraazacyclotetra-deca-4,11-diene. We place our emphasis on the properties of the period of homogeneous oscillations. It is found that T depends on the initial concentrations of reactions: T(s) = 0.125[BrO3–]0–1.22[H2SO4]0–2.97[CH3COCOOH]00.73 mol dm–3)–3.46. The period is not perfectly constant. The effects of concentrations of the components on the waveforms are also discussed.